Participatory organizational intervention for improved use of assistive devices for patient transfer: study protocol for a single-blinded cluster randomized controlled trial. Issue 1 (December 2016) - Jakobsen, Markus; Aust, Birgit; Dyreborg, Johnny; Kines, Pete; Illum, Maja; Andersen, Lars
Abstract Background Epidemiological studies have shown that patient transfer is a risk factor for back pain, back injuries and long term sickness absence, whereas consistent use of assistive devices during patient transfer seems to be protective. While classical ergonomic interventions based on education and training in lifting and transferring techniques have not proven to be effective in preventing back pain, participatory ergonomics, that is meant to engage and motivate the involved parties while at the same time making the intervention maximally relevant, may represent a better solution. However, these findings are largely based on uncontrolled studies and thus lack to be confirmed by studies with better study designs. In this article, we present the design of a study which aims to evaluate the effect and process of a participatory organizational intervention for improved use of assistive devices. Methods The study was performed as a cluster randomized controlled trial. We recruited 27 departments (clusters) from five hospitals in Denmark to participate in the study. Prior to randomization, interviews, observations and questionnaire answers (baseline questionnaire) were collected to gain knowledge of barriers and potential solutions for better use of assistive devices. In April 2016, the 27 departments were randomly allocated using a random numbers table to a participatory intervention (14 clusters, 324 healthcare workers) or a control group (13 clusters, 318 healthcare workers). The participatory intervention will consist of workshops with leaders and selected healthcare workers of each department. Workshop participants will be asked to discuss the identified barriers, develop solutions for increasing the use of assistive devices and implement them in their department. Use of assistive devices (using digital counters -, primary outcome, and accelerometers and questionnaire - secondary outcome), perceived physical exertion during patient transfer, pain intensity in the lower back, occurrence of work-related back injuries during patient transfer, organizational readiness to change, knowledge on how to perform proper patient transfer, social capital and work ability (secondary outcomes) were assessed at baseline and will also be assessed at 1 year follow-up. Process evaluation will be based on qualitative and quantitative data to assess the implementation, the change process, and the impact of context aspects. Discussion The study will evaluate the effect and process of a participatory intervention on improving the use of assistive devices for patient transfer among hospital healthcare workers. By using cluster-randomization, as well as process- and effect evaluation based on objective measures we will contribute to the evidence base of a promising intervention approach. Trial registration ClinicalTrials.gov (NCT02708550 ). March, 2016.